2020
DOI: 10.1111/papt.12269
|View full text |Cite
|
Sign up to set email alerts
|

Investigating self‐concept in self‐harm: A repertory grid study

Abstract: Objectives. The way that individuals perceive themselves and others may be relevant in understanding difficulties with self-harm. Repertory grids provide a relatively underutilized means of investigating self-concept in people who self-harm. This study aimed to examine the association between self-concept, captured through a repertory grid method, and self-harm.Method. Ninety-eight participants with a history of self-harm took part in the study. A repertory grid was used to derive distances between four elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
1
6
0
2
Order By: Relevance
“…Finally, recent work on self-concept content and NSSI has utilized repertory grid analysis (i.e., an analytic technique examining participants' perceived similarities across constructs via 'distances' within construed space) to examine NSSI in relation to peoples' perceptions of their current self, ideal self, identification of oneself as someone who self-injures, and identification with others who self-injure (Taylor, Usher, Jomar, & Forrester, 2020). NSSI recency (within the past year) was associated with less perceived similarity between one's current and ideal self, as well as greater similarity between one's current self and others with NSSI.…”
Section: Self-concept and Nonsuicidal Self-injury 17mentioning
confidence: 99%
“…Finally, recent work on self-concept content and NSSI has utilized repertory grid analysis (i.e., an analytic technique examining participants' perceived similarities across constructs via 'distances' within construed space) to examine NSSI in relation to peoples' perceptions of their current self, ideal self, identification of oneself as someone who self-injures, and identification with others who self-injure (Taylor, Usher, Jomar, & Forrester, 2020). NSSI recency (within the past year) was associated with less perceived similarity between one's current and ideal self, as well as greater similarity between one's current self and others with NSSI.…”
Section: Self-concept and Nonsuicidal Self-injury 17mentioning
confidence: 99%
“…An unstable sense of self may contribute to more negative self-perceptions as studies have found associations between poor SCC and lower self-esteem (an affective evaluation of self) and reduced self-certainty [ 75 , 76 ], which are theorized to leave individuals vulnerable to negative self-appraisals. Recent work has also shown connections between poor SCC and NSSI [ 57 , 65 , 66 ]. In a sample of 147 college students, Lear and Pepper [ 39 ] found that NSSI engagement and severity was associated with lower SCC.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, extroverted, risk-taking, aggressive, and outgoing players with tattoos were shown to be more successful in forward positions than those in defensive positions [34]. Nevertheless, in both men and women, tattooing accentuates their own sexual perceptions about sexual attractiveness and potency [33,35]. Women were reported to be more sexually active if they had tattoos, and a certain number of tattoos was associated with the number of premarital sexual partners and age at first intercourse both in men and women [36].…”
Section: Emotions and Motivations In Tattooed Peoplementioning
confidence: 97%
“…Women are more likely to have tattoos for body decoration, while men are more likely to have an image or symbol representing group identity [2]. One recent study revealed that women with tattoos tend to perceive the ideal body image as being a tattooed body [33]. Another investigation reported that female footballers prefer smaller and also more discreet tattoos for the purpose of ornamentation, while male footballers choose extensive tattoos, possibly to enhance their domination.…”
Section: Emotions and Motivations In Tattooed Peoplementioning
confidence: 99%